Исследование массовой скорости выгорания древесины, огнезащищённой гелеобразующей системой MgCl₂ + Na₂O · 2,7 SiO₂ - Киреев, А. А.; Тарасова, Г. В.; Жерноклёв, К. В. (НТУ "ХПИ", 2006)
Для цілей вогнезахисту та вогнегасіння горючих матеріалів запропоновано використовувати гелеутворюючи системи. Термогравіметричним методом досліджена кінетика процесу горіння деревини обробленої гелеутворюючей системою MgCl₂ + Na₂O · 2,7 SiO₂. Встановлені фактори що впливають на масову швидкість вигорання деревини.

For fireproofing suppressing of fires of flammable materials it is proposed to use gel-forming system. By the means of thermogravimetric techniques it was explored the kinetics of combustion of treated by gel-forming system MgCl₂ + Na₂O · 2,7 SiO₂ wood. It is determined the matters affecting the mass rate of burning out of wood.
Keywords: термогравиметрический эксперимент; коэффициент вспучивания; древесина; огнезащитные гели; выгорание; гель